'I hope you like jabbing, too'. The Covid vaccination campaign in Italy and the measures to promote compliance. Issue 2 (3rd April 2022) - Profeti, Stefania
ABSTRACT: From the start of 2021, the vaccination campaign against SARS-CoV-2 was high on the agenda of governments everywhere and the Italian Government was no exception. In this article, we shall describe the progress of the anti-Covid vaccination campaign in Italy with a particular focus on the policy tools adopted by the Government to encourage citizens' compliance and to combat reluctance. After considering the problem of engaging with the vaccination campaign using the analytic framework provided by studies of compliance, focus will be first on how the targets of the vaccination campaign came to be defined and the infrastructural facilities for administering the doses established, and then on the measures the Government took to overcome popular resistance to the vaccines and to maximise compliance, considering them in terms of their degree of 'intrusiveness'. In the final section, we conclude by highlighting the strengths and weaknesses of the campaign and by offering an assessment of the coherence and the timing of the Government's measures.